Pengaruh Kedisiplinan dan Minat Belajar Siswa Terhadap Prestasi Belajar Mata Pelajaran Al-Qur’an dan Hadits Di MTs. Ma’arif 20 Islamiyah Paloh Paciran Lamongan - Fuad, Zainul (MADINAH, 2015)
Education is the process by which a person is taught to be loyal and obedient and also his mind is nurtured and developed. Education is essentially something of a conscious and deliberate activity, and full of responsibility done by an adult to a child so that interaction arises from both in order for the child to reach the desired and continuous maturity. Therefore education is considered one of the aspects that have a fundamental role in shaping the next generation. With education is expected to produce human quality and responsible and able to anticipate the future. Given the very importance of education should be done as well as possible so as to obtain the expected results. School as a formal institution is the place that allows one to increase knowledge, and it is easiest to foster young people who are implemented by government and society.